Metronomic therapy in advanced breast cancer and NSCLC: vinorelbine as a paradigm of recent progress. Issue 1 (2nd January 2021) - Xu, Binghe; Sun, Tao; Wang, Shusen; Lin, Yingcheng
ABSTRACT: Introduction: Metronomic chemotherapy (MCT) is based on frequent dosing of the drug. . This leads to pharmacologically active but low plasma concentrations that reduce toxicity. MCT seems to work primarily via indirect effects on tumor cells and their microenvironment, rather than direct antitumor effects. Oral vinorelbine is one of the most widely studied MCT approaches in both advanced breast cancer and non-small cell lung cancer. Expert opinion: MCT with vinorelbine has proven efficacy, tolerability and quality of life benefits both as monotherapy and in combination with other MCTs or targeted agents, in first-line therapy and in previously treated patients. Key populations are emerging who may be particularly well suited to metronomic vinorelbine, including those with indolent disease, older individuals, and those with multiple comorbidities and/or bone metastases. Ongoing trials should help to further delineate these target groups. Additional work is needed to better understand the optimal vinorelbine regimen, particularly when used in combination or in non-Caucasian patients. Markers are also required to help identify individuals who are most likely to respond. Nonetheless, the efficacy and tolerability of MCT, allied to improved patient convenience, reduced need for medical engagement and lower cost, make it an appealing option – particular in resource-constrained healthcare environments.